1990
DOI: 10.7589/0090-3558-26.2.214
|View full text |Cite
|
Sign up to set email alerts
|

A Medium for the Selective Isolation of Edwardsiella Ictaluri

Abstract: A selective medium, called Edwardsiella ictaluri medium (EIM), has been formulated for the isolation of Edwardsiella ictaluri. The medium inhibits the growth of most gram-negative bacteria, except Proteus sp., Serratia marcescens and some isolates of Aeromonas hydrophila and Yersinia ruckeri. The bacteria that grow on the EIM are easily differentiated from E. ictaluri based on colony morphology. The EIM inhibits gram-positive bacteria with the exception of enterococci. The addition of fungizone to EIM suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…The E. ictaluri O-chain was found to be an unbranched linear polymer of a repeating tetrasaccharide unit composed of D-glucose, 2-acetamido-2-deoxy-D-galactose and D-galactose in a 1 : 2 : 1 ratio having the structure: (Vinogradov et al, 2005). Serological analyses using monoclonal antibodies have indicated that E. ictaluri is serologically homogeneous (Bertolini et al, 1990;Shotts & Waltman, 1990), suggesting that there is no variation in the O-PS between E. ictaluri strains.…”
Section: Introductionmentioning
confidence: 99%
“…The E. ictaluri O-chain was found to be an unbranched linear polymer of a repeating tetrasaccharide unit composed of D-glucose, 2-acetamido-2-deoxy-D-galactose and D-galactose in a 1 : 2 : 1 ratio having the structure: (Vinogradov et al, 2005). Serological analyses using monoclonal antibodies have indicated that E. ictaluri is serologically homogeneous (Bertolini et al, 1990;Shotts & Waltman, 1990), suggesting that there is no variation in the O-PS between E. ictaluri strains.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of SW medium, there have been important observations on its preparation and use. The original paper gave a percentage of 0.0003% for bromthymol blue, which was subsequently confirmed to be an error and should be 0.003% (Shotts, 1991). Even with the correct percentage, in most instances, the medium is pale yellow at the specified pH of 7.4.…”
Section: Yersinia Ruckerimentioning
confidence: 99%
“…Selective and differential media are available to aid with primary isolation of Aeromonas spp. from fish, including Rimler-Shotts (RS; Shotts and Rimler, 1973) and SGAP-10C (starchglutamate-ampicillin-penicillin, 10 mg/L C from glucose; Huguet and Ribas, 1991). SGAP-10C may also be used for isolation and quantification of the organisms from water (Jenkins and Taylor, 1995).…”
Section: Renibacterium Salmoninarummentioning
confidence: 99%
See 1 more Smart Citation
“…Sex, weight and total body length measurements were recorded, and fish examined for any external or internal gross abnormalities. For bacterial isolation, pooled kidney and spleen tissues from each individual were homogenised and inoculated onto blood agar (BA) and Edwardsiella ictaluri medium (EIM) (Shotts and Waltman 1990). Inoculated plates were couriered in sturdy insulated boxes under ambient temperatures to the Animal Health Laboratories, Department of Agriculture and Food Western Australia, Perth, and incubated at 24°C for 48 to 72 hours.…”
Section: Samplingmentioning
confidence: 99%